FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SEDIAAN MASKER GEL PEEL OFF EKSTRAK ETANOL DAUN PEGAGAN (Centella asiatica (L.) Urban) - Putri, Meilisa; Capritasari, Rafiastiana; Wijayatri, Ratna; Ningrum, Yessika Ardian; Pradani, Missya Putri Kurnia (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
Free radicals damage cellular structures and accelerate the degradation of important elements in the skin, thereby accelerating premature aging. Antioxidants in skin care products can shield cells from harm brought on by oxidative stress. Pegagan leaves (Centella asiatica (L.) Urban) are a natural source of antioxidants. Pegagan leaf ethanolic extract has antioxidant properties and can perhaps be applied in cosmetic products like peel-off mask gel. The objective of this research is to measure the antioxidant behavior of a mask that peels off gel composed of ethanolic extract of Pegagan leaves (Centella asiatica (L.) Urban). This research applies a one-shot case study laboratory experimental method. Pegagan ethanolic extract was utilized in concentrations of F1 (0.5% ) F2 (1%) and F3 (1.5%). The level of antioxidant activity was measured. for three formulae using the DPPH (2,2-diphenyl-1-picrylhydrazyl) technique. Organoleptic, pH measurement, viscosity, homogeneity, spreadability, and drying time are all considered in the physical evaluation of the preparation. Based on evaluation outcomes of the preparations, three formulas met the test requirements with organoleptic test parameters, a drying time of 15-30 minutes, and a pH value between 4.5 and 6.5. For the spreadability test, only F2 meets the test requirements with 5-7 cm, while F1 and F3 do not follow the criteria because the A preparation's spreadability is influenced by viscosity. The thicker the mask gel preparation, the smaller the resulting spreading area. The result examination for antioxidant activity on the ethanolic extract Pegagan leaf showed an IC50 value for F1 of 28.68 ppm, F2 of 38.51 ppm, and F3 of 48.68 ppm. Study shows making the peel-off mask prepared gel Pegagan ethanol extract meets the criteria for a strong antioxidant. The results of this research indicate the quantity of antioxidant function in addition to the outcomes of the physical assessment have an impact on the concentration of pegagan leaf extract in the gel mask that peels off.